Subscribe to our Youtube Channel - https://www.youtube.com/channel/UCZBx269Tl5Os5NHlSbVX4Kg

Slide5.JPG

Slide6.JPG
Slide7.JPG

  1. Chapter 2 Class 12 Inverse Trigonometric Functions
  2. Serial order wise

Transcript

Ex 2.2, 3 Prove tan−1 2/11 + tan−1 7/24 = tan−1 1/2 Solving L.H.S. tan-1 2/11 + tan−1 7/24 = "tan−1" ((2/11 + 7/24)/(1− 2/11 × 7/24)) We know that tan-1 x + tan−1 y = tan−1 ((𝒙+𝒚 )/(𝟏 −𝒙𝒚)) Replace x by 2/11 and y by 7/24 = tan-1 ((2/11 + 7/24)/(1− (7 × 1)/(11 × 12))) = tan-1 (((24 × 2 + 7 × 11)/(24 × 11))/((11 × 12 − 7)/(11 × 12))) = tan-1 (((48 + 77)/(24 × 11))/((132 − 7)/(11 × 12))) = tan-1 ((125/(24 × 11))/(125/(11 × 12))) = tan-1 (125/(24 × 11) × (11 × 12)/125) = tan−1 (1/2) = R.H.S. Hence. R.H.S. = L.H.S. Hence Proved

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.